Sufistikasi Kekuasaan Pada Kesultanan Riau-Lingga Abad XVIII-XIX M - Achmad Syahid (Ulumuna, 2005)
The development of Islam in most parts of Indonesia, such as in Malay, is almost undistinguishable with the political development. There was a good relationship between sultan as the holder of political authority and ‘ulamâ’ as the holder of religious authority symbolized as “one diamond in one ring”. To strengthen his power, a sultan needs legitimacy from ‘ulamâ’ and vice versa, through a close reltionship with the sultan, an ulama can increase his religious authority. Based on the historical analyses, especially on the case of Sultanate of Riau-Lingga in the 18th-19th centuries, the relationship between ulama and sultan was not always in harmony as previously described. The relationship sometime depended on their needs, which from time to time, competitive, cooperative and contestive. Apart from any forms of relationship, this article reveals that there was a “sufistication” process occurred where the political power which was characteristically profane and secular, changed as an influence of the sufism teachings. Thus, what happened in Sultanate of Riau-Lingga proved that sufism is an important phenomenon which changed the historical color and intellectual literature in Indonesia